Reflections on the Utilization of Flat Style Illustration in Landscape Design - Luo, Heng (Journal of China-ASEAN Studies, 2024)
In creative practice, the articulation of landscape effects holds paramount importance, necessitating designers to master a variety of representational forms, such as plan drawings, perspective views, 3D animations, and physical models. This demands designers to possess a solid artistic foundation, a cultivated sense of appreciation, and an innovative spirit. This paper aims to explore flat-style illustration as an emerging paradigm for landscape effect representation, analyzing its applications and advantages in design practice. By briefly elucidating the fundamental concepts and application scope of flat-style illustration, the study conducts an in-depth analysis through relevant case studies. Research indicates that flat-style illustration exhibits distinctive advantages in landscape effect representation, including visual simplicity and efficiency in information transmission, which effectively enhances the expressive power of design. These findings provide theoretical support for designers in applying flat-style illustration in landscape effect creation, thus advancing the development of this emerging representational paradigm.